UPAYA PENINGKATAN FASILITAS PEJALAN KAKI DI KAWASAN DUKUH ATAS DENGAN MENGGUNAKAN METODE IMPORTANCE PERFORMANCE ANALYSIS - M. Aqil Ash Shiddieqy; Endrawati Fatimah; Martina Cecilia Adriana (Universitas Trisakti, 2022)
Public transport integration is the key to the success of the public transportation service system in a region or city. Good integration can create effective development and increase society's interest in public transport. Dukuh Atas area is located in the Central Business District of Jakarta that dominated by office buildings and activities. This area is designated as a primary activity centre with an intermodal transfer centre based on Transit Oriented Development (TOD). It consists of several stops/stations such as Sudirman Commuter line Station, BNI City Airport Train Station, Dukuh Atas MRT Underground Station, Dukuh Atas 2 Transjakarta Bus Stop, and Tosari Bus Stop. Pedestrian paths are one of the physical integration forms that play a role in creating continuous connectivity. This study aims to measure the service level of pedestrian lane facilities in supporting intermodal integration in the Dukuh Atas area. The data used in this study are primary data gathered through observations and questionnaires. The questionnaires use a Likert scale of 1-5 distributed to 112 pedestrians in 3 segments (1) MRT – KRL, (2) MRT – TransJakarta, and (3) KRL – TransJakarta. Data analysis was conducted with the Importance Performance Analysis. Results show that three similar facilities were found to be the improvement priority in all three segments that are lighting, canopy, and trash bins. Moreover, other facilities that need to be improved are the sidewalk width in segment 1, directions in segment 2, and pedestrian crossing bridge/zebra cross in segment 3.